The Impact of Competency Entrepreneurship on Micro, Small, Medium Enterprises Performance - Elsa Nanda Utami; Hendrati Dwi Mulyaningsih (Research Synergy Foundation, 2017)
This reasearch is conducted on MSME (Micro Small Medium Enterprises) that are participated in the MSME Syari’ah Mentoring Program by Academition and Practitioners (PUSPA) organized by Bank Indonesia in Bandung. MSME who participated in PUSPA program 2016 is MSME that included in necessity entrepreneur where MSME operated just to fullfil the life necessities. This program aims to improve the competence of entrepreneurship owned by MSME in term of knowledge, attitudes, and skills. Increased in the entrepreneurial comptence will have an impact on MSME perfomance both on financial term by the increase in income and non-financial term namely by the increased of the knowledge and skills like simple accounting, managing the production process, how to market the product, and know the procedures for obtaining the venture capital. The purpose of this reasearch was to investigate the influence of the entrepreneurial competence on the MSME performance in PUSPA program 2016. Researcher used quantitative research method. This research use sampling technique on non-probability sampling that is saturated sampling because the members of population less than 30 people and the entire population is a sample. Total sample in this research is 20 respondents. Data collecting in this research is done by distributing questionarries to all respondents that is MSME that pariticaped in PUSPA program 2016. Data were analyzed using simple regression analysis and descriptive-causal analysis. The result showed that entrepreneurial competenec affect the performance of MSME that participated in PUSPA Program 2016. Based on the calculation, coefficent of determination (R2) can be seen the influence of entrepreneurial compentence variable (X) on the performance (Y) is 61.7%. While the remaining 38.3 is influenced by other factors such as mentoring, motivation, and human resources.